Curcumin Nanoemulsion: Unveiling Cardioprotective Effects via ACE Inhibition and Antioxidant Properties in Hypertensive Rats - Mohd Ishaq; Mohemmed Faraz Khan; Garima Verma; Akshoo Rathi; Mohammad Adil; Mohammad Faizan; Abul Kalam Najmi; Mohd Akhtar; Omkulthom Al kamaly; Samar Zuhair Alshawwa; Abdelaaty A. Shahat; Abdulsalam Alhalmi (Medicina, 2023)
Background and Objectives: Curcumin, derived from Curcuma longa, is a well-known traditional medicinal compound recognized for its therapeutic attributes. Nevertheless, its efficacy is hampered by limited bioavailability, prompting researchers to explore the application of nanoemulsion as a potential alternative. Materials and Methods: This study delves into the antihypertensive effects of curcumin nanoemulsion (SNEC) by targeting the renin-angiotensin-aldosterone system (RAAS) and oxidative stress in deoxycorticosterone acetate (DOCA) salt-induced hypertensive rats. To gauge the cardio-protective impact of SNEC in DOCA salt-induced hypertension, molecular docking was undertaken, uncovering curcumin’s high affinity and adept binding capabilities to the active site of angiotensin-converting enzyme (ACE). Additionally, the investigation employed uninephrectomized rats to assess hemodynamic parameters via an AD instrument. Serum ACE, angiotensin II, blood urea nitrogen (BUN), and creatinine levels were quantified using ELISA kits, while antioxidant parameters were evaluated through chemical assays. Result: The outcomes of the molecular docking analysis revealed robust binding of curcumin to the ACE active site. Furthermore, oral administration of SNEC significantly mitigated systolic, diastolic, and mean arterial blood pressure in contrast to the DOCA-induced hypertensive group. SNEC administration also led to a reduction in left ventricular end-diastolic pressure (LVEDP) and an elevation in the maximum rate of left ventricular pressure rise (LV (dP/dt) max). Moreover, SNEC administration distinctly lowered serum levels of ACE and angiotensin II compared to the hypertensive DOCA group. Renal markers, including serum creatinine and BUN, displayed a shift toward normalized levels with SNEC treatment. Additionally, SNEC showcased potent antioxidant characteristics by elevating reduced glutathione, catalase, and superoxide dismutase levels, while decreasing the concentration of thiobarbituric acid reactive substances. Conclusions: Collectively, these findings underscore that curcumin nanoemulsion exerts noteworthy cardio-protective effects through ACE activity inhibition and remarkable antioxidant properties.